Göz Brakiterapisinde Kullanılan 142pr Radyoizotopunun Üretilmesi Ve Monte Carlo Yöntemiyle Doz Değerlendirmesi - Koyuncu, Neslihan (Enerji Enstitüsü, 2019)
Son yıllarda dünya genelinde kansere yakalananların ve kanser nedeni ile ölenlerin sayısında artma söz konusudur. Bu artışın bir çok nedeni olmasına karşın araştırmacıların ilgilendiği nokta kanserli hücrelerin bölünmesini durdurmak ve kanserli hücreyi yok etmektir. Araştırmacıların, günümüzün en önemli hastalıklarından olan kansere karşı tedavi bulma ve üzerinde çalışma konusunda ilgileri artmıştır. Artan çalışmalar sayesinde farklı yöntemler ile kanserli hücreleri yok etme şansı doğmuştur. Kanserde cerrahi müdahale ve kemoterapi gibi geleneksel tedavilerin yanı sıra radyasyon ve radyoaktif kaynakların sağlık alanında kullanılmaya başlanmasıyla yeni tedavi yöntemleri ortaya çıkmıştır. Yüksek veya düşük dozda radyasyon uygulanarak yapılan ve radyoterapi olarak adlandırılan tedaviler ile kanserli hücrelerin çoğalması ve azalması hatta tamamen yok olması hedeflenmiştir. Uygulanan bu radyasyonun kaynağı bir lineer hızlandırıcı veya doğrudan radyoaktif kaynaktan gelebilmektedir. Hızlandırıcı ile yapılan tedaviler dış ışın radyoterapisi, kaynaktan gelen radyasyonla yapılan tedaviler ise brakiterapi olarak adlandırılır. Bu tezde üzerinde çalışılan brakiterapi, tümörün içine veya yakınına radyoaktif kapsül koyularak yapılan tedavi şeklidir. Belirli kanser çeşitleri için veya belirli boyuttaki tümörlerde kullanılabilen brakiterapide amaç sağlıklı dokulara en az hasarı verirken tedavi edilecek olan bölgeye en fazla dozu vermektir. Yapılan literatür araştırmaları sonucunda brakiterapide kullanılan çok çeşit radyoizotop olduğu saptanmıştır. Beta ışını yayınlayan; 32P, 90Y, 90Sr, x-ışını ve gama ışını yayınlayan; 125I, gama ışını yayınlayan; 192Ir kullanılan brakiterapi kaynakları arasındadır. Ancak yeni kullanılmaya başlanan ve üzerinde yapılan çalışmalar devam eden bir beta kaynağı bu kaynakların önüne geçerek brakiterapide iyi bir radyoizotop olacağını gösterdi. Bu radyoizotop Praseodimiyum-142'dir. Son zamanlarda brakiterapide artan ilgisiyle 142Pr, yaklaşık olarak % 96,3 beta ışınımı yapan, % 3,7 gama ışınımı yapan bir radyoizotoptur. 141Pr'in (n,γ) reaksiyonu sonucunda oluşan 19,12 saat yarı ömrü olan 142Pr, bu özelliği ile hedefe yüksek doz vermesini sağlar. Beta ışınımı yaptığı için dokuya giriciliği kısıtlıdır, bu nedenle hedefin etrafındaki dokuya en az hasarı verir. 142Pr, 11,40 barn tesir kesitine sahip olduğu için düşük nötron akıcılığına sahip olan bir reaktörde bile üretimi mümkündür. Bu çalışmada 142Pr radyoizotopu İTÜ TRIGA Mark II eğitim ve araştırma reaktöründe üretildi. Üretilen 0,9 cm uzunluğunda, 0,04 cm yarıçapında silindir şeklindeki 142Pr radyoaktif tohumunun aktivitesi 3,48 mCi'dir. Ancak hastaya uygulanabilirliğine göre aktivite hesabının yapılması daha doğrudur. Bu nedenle radyoaktif tohum üretildikten 5 saat sonraki aktivitesi hesaplandı ve çalışmalar bu aktiviteye göre yapıldı. 142Pr tohumunun üretiminden 5 saat sonraki aktivitesi 2,89 mCi'dir. Üretilen 142Pr tohumunun dozimetrik karakterini incelemek için MCNP'de (Monte Carlo N-parçacık kodu) simülasyon gerçekleştirildi. Aynı ölçülerde radyoaktif tohum MCNP'de modellendi. 0°'den 90°'ye kadar 10'ar derecelik açılarla ve 0,1 cm'den 0,8 cm'e kadar 0,1'er cm aralıklar ile radyal mesafelere yerleştirilen dedektörler sayesinde doz dağılımı incelendi. Her bir açıda bulunan dedektör için radyal doz profili oluşturuldu. Amerikan Tıp Fizikçiler Birliği (AAPM) Radyasyon Terapi Komitesi'nin brakiterapi kaynakları için yayınladıkları dozimetri protokolü uygulandı. AAPM Görev Grubu 60 ve Görev Grubu 43'e göre tanımlanan dozimetrik parametreler, geometri fonksiyonu, radyal doz fonksiyonu ve 2 boyutlu anizotropi fonksiyonu hesaplandı. Hastanın alacağı 142Pr brakiterapisinden kaynaklanan doz, bu görev gruplarından da elde edildi. 142Pr radyoaktif tohumu beta ışınımı yapan bir radyoizotop olduğu ve bu nedenle doku içerisindeki menzili kısa olduğu için yüzeysel tümörlerde ve gözde meydana gelen tümörlerde kullanılabilir. Göz, radyasyona çok duyarlı bir organ olduğu için gözde bulunan bir kanseri yok ederken etrafındaki dokulara zarar gelmemesi çok önemlidir. Bu nedenle 142Pr radyoizotopu, göz kanserini tedavi etmek için kullanılabilir. Dozimetrik parametreleri oluşturulan 142Pr radyoizotopunun göz içerisindeki doz dağılımını incelemek için MCNP'de göz modellemesi yapıldı. Modellenen gözün yarıçapı 2 cm'dir ve sudan oluşmaktadır. Brakiterapi sırasında gözün alacağı dozları incelemek için MCNP'de dedektörler oluşturuldu. Bu dedektörler 0°, 30°, 60° ve 90°'lerde, 0,1 cm'den 0,9 cm'e kadar 0,1'er cm aralıklar ile radyal mesafelere yerleştirildi. Her açı için radyal doz profili çıkartıldı. Elde edilen sonuçlar doğrultusunda, 142Pr radyoaktif tohumunun gözün yüzeyine yüksek doz vererek sağlıklı dokulara en az zararı verdiği için göz brakiterapisinde iyi bir radyoaktif kaynak olduğu bu çalışmada saptanmıştır.

In recent years, there has been an increase in the number of people who get cancer and die from cancer worldwide. Although there are many reasons for this increase, researchers are interested in stopping and destroying the division of cancerous cells. Researchers' interest in finding and working on cancer treatment which is one of the most important diseases, has increased. Thanks to the increasing number of studies, it has been possible to destroy cancerous cells by different methods. In addition to traditional treatments in cancer such as surgical intervention and chemotherapy, the beginning of using radiation and radioactive sources in the field of health has emerged new treatment methods. By applying high or low doses of radiation to the area to be treated which is called radiotherapy, cancerous cells are aimed to decrease or even completely disappear. The source of this radiation may be coming from a linear accelerator or a direct radioactive source. The treatments with the accelerator are called external beam radiotherapy and the treatments with radiation from the source are called brachytherapy. The brachytherapy studied in this thesis is the treatment by placing a radioactive capsule in or near the tumor. Brachytherapy, which can be used for certain types of cancers or a certain size of tumors, also aims to give the highest dose to the area to be treated while giving the least damage to healthy tissues. As a result of literature researches, it is determined that there are many kinds of radioisotopes used in brachytherapy. Beta-emitting radioisotopes; 32P, 90Y, 90Sr, x-ray and gamma-emitting radioisotope; 125I, gamma-emitting radioisotope; 192Ir are using for brachytherapy. However, a beta source that has just started to be used and studies on it has been shown to be a good radioisotope in brachytherapy. This radioisotope is Praseodymium-142. Recently, with increasing interest in brachytherapy, 142Pr is a radioisotope that emits approximately 96.3% beta radiation and 3.7% gamma radiation. Its maximum beta energy is 2.162 MeV and its maximum gamma energy is 1.575 MeV. 142Pr radioisotope is produced by a reaction which is 141Pr (n, γ) 142Pr. As a result, 142Pr has 19.12 hours of half-life time. Because of its short half-life, it gives high doses to the target. Due to its beta radiation, its penetration into the tissue is limited, so it gives minimal damage to the tissue around the target. Its range in water is 10.3 mm. Since 142Pr has a cross-section of 11.40 barn, it is possible to produce even in a reactor with low neutron fluency. In this study, 142Pr radioisotope was produced in ITU TRIGA Mark II education and research reactor. The produced cylindrical 142Pr radioactive seed which has a dimension that 0.9 cm long and radius of 0.04 cm, has an activity of 3.48 mCi. However, it is more accurate to calculate activity according to the applicability to the patient. Therefore, the activity was calculated 5 hours after the production of radioactive seed and the studies were performed according to this activity. The activity of 142Pr seed 5 hours after production is 2.89 mCi. To calculate these activities, the thermal and epithermal flux of the reactor should be known. The neutron flux is determined using the gold foil activation method with 197Au (n, γ) 198Au reaction. Two types of samples are prepared for this neutron flux determination; unsheathed gold foil and cadmium coated gold foil. These gold foils are used in this method because the cadmium is known as a thermal neutron filter. Cadmium holds the thermal neutron, allowing only the epithermal neutron to pass. Since bare gold foil was activated both thermal and epithermal neutrons, when the activations of these two samples are subtracted from each other, the result will be the activation of the thermal neutron. As a result, the thermal neutron flux of the reactor is 1.43x1012 n/cm2s and the epithermal neutron flux of the reactor is 1.26x1011 n/cm2s. Simulations were performed using the MCNP5 code to examine the dosimetry character of the 142Pr seed. MCNP is a general Monte Carlo transport code that solves the time-dependent continuous energy transition of neutrons, photon and electrons in 3D geometry. The purpose of the MCNP code is to use nuclear and the atomic information library. Using MCNP code, radiation protection and dosimetry, radiation shielding, radiography, medical physics, nuclear critical safety, accelerator design, fission and fusion reactor design applications can be made. For examining the dosimetric character, firstly, the same size radioactive seed produced at ITU TRIGA Mark II reactor was modeled with MCNP5 code. In the model for 142Pr radioactive seed, it consists of 3 cells, 74 detector cells and 78 surfaces. A spherical water detector with a radius of 0.01 cm was used to calculate the dose per unit activity at different distances and angles. Dose distribution was examined by detectors placed at radial distances from 0.1 cm to 0.8 cm and angles at 0 ° to 90 °. The radial dose profile was created for the detector at each angle. The American Society of Medical Physicists (AAPM) Radiation Therapy Committee published a dosimetry protocol for brachytherapy sources. Dosimetric parameters, geometry function, radial dose function and 2D anisotropy function were calculated according to AAPM Task Group 60 and Task Group 43. The dose that caused by brachytherapy was also obtained from these task groups. 142Pr radioactive seed is a beta-emitting radioisotope and therefore it has a short range in tissue. Because of this feature, it can be used in superficial tumors and tumors at the eye. Because the eye is a very sensitive organ to radiation, the surrounding tissue must not be damaged while destroying a cancerous cell in the eye. Thus, 142Pr can be used to treat eye cancer. In order to examine the dose distribution of 142Pr radioisotope within the eye whose dosimetric parameters were generated, eye modeling was performed using with MCNP5 code. The radius of the modeled eye is 2 cm and it consists of water. Detectors were created in MCNP to examine the doses of the eye during brachytherapy. These detectors were placed at 0°, 30°, 60°, and 90° angles and radial distances with 0.1 cm to 0.9 cm. The radial dose profile was extracted for each angle. The results showed that 142Pr radioactive seeds would be a good source in eye brachytherapy because it gives high doses to the surface of the eye but gives minimal damage to healthy tissues.
Production Of 142pr Radioisotope And Its Dose Evaluation by Monte Carlo Method In Eye Brachytherapy Applications
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Enerji Enstitüsü, 2019
Thesis (M.Sc.) -- İstanbul Technical University, Energy Institute, 2019
Keywords: Radyasyon; Monte Carlo yöntemi; Radiation; Monte Carlo method